Self-efficacy and entrepreneurial performance of start-ups - Marco Caliendo; Alexander S. Kritikos; Daniel Rodríguez; Claudia Stier (Small Business Economics, 2023)
Abstract Self-efficacy reflects the self-belief that one can persistently perform difficult and novel tasks while coping with adversity. As such beliefs reflect how individuals behave, think, and act, they are key for successful entrepreneurial activities. While existing literature mainly analyzes the influence of the task-related construct of entrepreneurial self-efficacy, we take a different perspective and investigate, based on a representative sample of 1,405 German business founders, how the personality characteristic of generalized self-efficacy influences start-up performance as measured by a broad set of business outcomes up to 19 months after business creation. Outcomes include start-up survival and entrepreneurial income, as well as growth-oriented outcomes such as job creation and innovation. We find statistically significant and economically important positive effects of high scores of self-efficacy on start-up survival and entrepreneurial income, which become even stronger when focusing on the growth-oriented outcome of innovation. Furthermore, we observe that generalized self-efficacy is similarly distributed between female and male business founders, with effects being partly stronger for female entrepreneurs. Our findings are important for policy instruments that are meant to support firm growth by facilitating the design of more target-oriented offers for training, coaching, and entrepreneurial incubators.
Additional information: L26;M13;D91
Keywords: 330; Entrepreneurship; Firm performance; General self-efficacy; Survival; Job creation; Innovation